A bargaining game-based profit allocation method for the wind-hydrogen-storage combined system. (15th March 2022) - Wang, Xuejie; Li, Bingkang; Wang, Yuwei; Lu, Hao; Zhao, Huiru; Xue, Wanlei
Highlights: Constructed a wind-hydrogen-storage combined system with low-carbon characteristics. Dispatching of wind-hydrogen-storage combined system based on DRO model. A profit allocation model is proposed based on the bargaining game theory. Abstract: Aiming at the coexistence of multiple players in the wind-hydrogen-storage combined system, a new profit allocation mechanism is proposed. The combination of multiple stakeholders such as wind power plant (WT), hydrogen energy system (HE), and energy storage system (ES) can achieve the purpose of promoting renewable energy consumption by using renewable energy to produce hydrogen, so as to improve overall system benefits. However, WT, HE, and ES belong to different stakeholders, and wind output is uncertain, which affects the efficient operation of the wind-hydrogen-storage combined system. Based on this, firstly, the Wasserstein metric is used to characterize the ambiguity set of the probability distribution of wind output forecast error, and a distributionally robust optimization model considering the uncertainty of wind output and demand response is constructed to maximize the benefits of the wind-hydrogen-storage combined system. Secondly, in order to balance the profits of multiple players in the combined system, a profit allocation model considering the real contribution of each player is proposed based on the Nash-Harsanyi bargaining game theory. Finally, the effectiveness of the proposed distributionally robust optimization operation model and profit allocation method are verified by simulation in a typical wind-hydrogen-storage combined system.